2023
DOI: 10.3390/life13020292
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Manual Therapy Approaches on Pain, Maximum Mouth Opening and Disability in Temporomandibular Disorders: A Systematic Review of Randomised Controlled Trials

Abstract: Temporomandibular disorder (TMD) is a common condition disabling people and bringing up costs. The aim of this study was to investigate the effects of manual therapy on pain intensity, maximum mouth opening (MMO) and disability. Searches were conducted in six databases for randomised controlled trials (RCTs). Selection of trials, data extraction and methodological quality assessment were conducted by two reviewers with discrepancies resolved by a third reviewer. Estimates were presented as mean differences (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Temporomandibular disorders (TMDs) are a group of disorders affecting the temporomandibular joint (TMJ) and the muscles that control its movements [1][2][3]. Typical symptoms of TMD are pain or tenderness in the preauricular area, difficulty opening or closing the mouth, and a clicking sensation within the TMJs [1,[4][5][6].…”
Section: Introduction 1rationalementioning
confidence: 99%
“…Temporomandibular disorders (TMDs) are a group of disorders affecting the temporomandibular joint (TMJ) and the muscles that control its movements [1][2][3]. Typical symptoms of TMD are pain or tenderness in the preauricular area, difficulty opening or closing the mouth, and a clicking sensation within the TMJs [1,[4][5][6].…”
Section: Introduction 1rationalementioning
confidence: 99%
“…Lastly, surgery is the final option in cases where rehabilitative techniques are not effective. Chiropractic therapy is a promising non-invasive approach that has been shown to manage TMD symptoms effectively [ 9 , 10 ]. In a recent meta-analysis of 20 randomized controlled trials, chiropractic therapy was shown to significantly improve measures of pain, maximum mouth-opening (MMO), and disability in TMD patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chiropractic therapy is a promising non-invasive approach that has been shown to manage TMD symptoms effectively [ 9 , 10 ]. In a recent meta-analysis of 20 randomized controlled trials, chiropractic therapy was shown to significantly improve measures of pain, maximum mouth-opening (MMO), and disability in TMD patients [ 9 ]. Furthermore, spinal manipulation and manual mandibular therapy were the most effective chiropractic techniques to treat TMD [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the multifactorial etiological characteristics, treatment should be initiated by minimally invasive and reversible therapies [13][14][15][16]. Among these treatments, the use of interocclusal splints [17], transcutaneous electrical nerve stimulation (TENS) [18], cognitive behavioral therapy [19], pharmacological therapy [20], acupuncture [21], manual therapies [22], ultrasound [23], and photobiomodulation (PBMT) [24] stand out.…”
Section: Introductionmentioning
confidence: 99%